2015
DOI: 10.1007/s11747-014-0423-4
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation, product portfolio innovativeness and firm performance: the dual role of new product development capabilities

Abstract: Despite a growing interest in the phenomenon of open innovation (OI), empirical evidence documenting the link between new product development capabilities, OI practices, and new product innovativeness is scarce. Eminent scholars have called for large-scale studies that systematically investigate the OI paradigm. Drawing on the knowledgebased view of the firm, new product development, and NPD capabilities literature streams, we conceptualize a framework in which OI practices are disentangled according to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 79 publications
(119 reference statements)
1
105
1
6
Order By: Relevance
“…However, this situation hinders the company's incremental innovation performance. Rubera et al (2016) found that, when complemented by market information and the strong involvement of the R&D department, OI practices positively influence the number of new-to-firm products that firms develop and introduce to markets.…”
Section: Incremental and Radical Innovation And Open Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this situation hinders the company's incremental innovation performance. Rubera et al (2016) found that, when complemented by market information and the strong involvement of the R&D department, OI practices positively influence the number of new-to-firm products that firms develop and introduce to markets.…”
Section: Incremental and Radical Innovation And Open Innovationmentioning
confidence: 99%
“…Several publications seek to demonstrate the main practices that companies operating in different countries and economic sectors adopt in order to operationalize OI (Van de Vrande et al, 2009;Cheng and Huizingh, 2014). Other studies show the influence of relationships between the application of OI practices and firm performance (Burcharth et al, 2014;Greco et al, 2015;Rubera et al, 2016). However, conclusions regarding the nature of the relationship remain uncertain (Cheng and Shiu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We collect data on new product launches in 51 countries from Mintel GNPD, 4 a database that records launches in the packaged food industry and provides a wide range of detailed information including price, packaging claims, and the date a new product is launched in a country. The prior studies using this database include Calantone et al (2014), Cillo et al (2018), and Rubera et al (2016). Mintel GNPD categorizes launches in five categories: New Product, New Packaging, New Variety, New Formulation, and Re-launch.…”
Section: Datamentioning
confidence: 99%
“…Innovation requires external learning, including market learning and network learning, and internal learning, including R&D. A firm must acquire information from every possible source in order to develop leading edge innovative products to fulfill the market's needs (Weerawardena, Mort, Liesch, & Knight, 2007). Recent studies have shown that expanding the scope of information from external ideas and technologies, enables firms with high flow of informational exchange to detect future market trends and develop innovations to capitalize on them (Rubera, Chandrasekaran, & Ordanini 2015;Zhou & Li, 2012). For instance, strong channel relationships increase international channel performance through reduced transaction related costs (Zhang, Cavusgil, & Roath, 2003).…”
Section: Research Hypothesesmentioning
confidence: 99%